Ecotoxicity and biodegradability of new brominated flame retardants: a review - Ezechiáš, M; Covino, S; Cajthaml, T (Ecotoxicology and environmental safety, 2014)
Brominated flame retardants (BFRs) have been routinely used as additives in a number of consumer products for several decades in order to reduce the risk of fire accidents. Concerns about the massive use of these substances have increased due to their possible toxicity, endocrine disrupting properties and occurrence in almost all the environmental compartments, including humans and wildlife organisms. Several conventional BFRs (e.g. polybrominated diphenylethers (PBDE)) have been included in the list of Persistent Organic Pollutants and their use has been restricted because of their established toxicity and environmental persistence. Over the past few years, these compounds have been replaced with "new" BFRs (NBFRs). Despite the fact that NBFRs are different chemical molecules than traditional BFRs, most of physical-chemical properties (e.g. aromatic moiety, halogen substitution, lipophilic character) are common to both groups; therefore, their fate in the environment is potentially similar to the banned BFRs. Therefore, this article has been compiled to summarize the published scientific data regarding the biodegradability of the most widely used NBFRs, a key factor in their potential persistency in the environment, and their ecotoxicological effects on humans and test organisms. The data reviewed here document that the mechanisms through NBFRs exibit their ecotoxicity and the processes leading to their biotransformation in the environment are still poorly understood. Thus emphasis is placed on the need for further research in these areas is therefore emphasized, in order to avoid the massive use of further potentially harmful and recalcitrant substances of anthropogenic origin.
Keywords: Environmental Exposure; bromované uhlovodíky; Flame Retardants; Environmental Monitoring; retardanty hoření; hodnocení rizik; Hydrocarbons, Brominated; Biodegradation, Environmental; Animals; lidé; Risk Assessment; monitorování životního prostředí; zvířata; biodegradace; Humans; vystavení vlivu životního prostředí